Study of predicting perinatal outcome in patients with oligohydraminos at term pregnancy - Damor, Jahanvi; Meena, Pooja; Thakkar, Bhoomika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Amniotic fluid plays a major role in the fetal growth and development. It provides the fetus with a protective low resistance environment suitable for growth and development, a cushion against the constricting confines of the gravid uterus, allowing the fetus room for the movement and growth and protecting it from external trauma. The abnormalities of the fluid volume can interfere directly with the fetal development or may be an indirect sign of underlying disorder such as fetal hypoxia, neural tube defect or gastrointestinal obstruction. Aim of this study was to determine whether an amniotic fluid level of 5cm or less can be predictor of adverse perinatal outcome in terms of fetal distress, birth weight, APGAR score and neonatal morbidity and mortality. Methods: Amniotic fluid index (AFI) was determined with a b-mode real time scanner with linear transducer operated at 3.5 MHz. AFI estimation done by four quadrant technique in supine position. The summation of measurement from each quadrant represented the amniotic fluid index in centimeters of each patient. Fetal outcome was assessed with respect to birth weight and gestational age; Apgar score at one and five minutes; any other neonatal complications intrapartum or postpartum during stay in hospital and maturity of baby - condition at the time of discharge of mother and baby. Results: The labor was induced in 28% women with AFI <5cm, out of which 19 women delivered vaginally and 9 women underwent LSCS for failure of induction. The mean birth weight was 2.61 kg in our study. Maximum number of babies i.e. 57% were with birth weight between 2.1-2.5 kg. The APGR score at 5 min was 9 in 71% cases and 8 in 21% cases. The mean APGR score at 5 min was 8.63. Conclusions: AFI can be used as an adjunct for fetal surveillance along with other methods to identify high risks foetuses to improve the perinatal outcome.